Populist Religion and Left-Wing Politics in France, 1830-1852 - Berenson, Edward (Princeton : Princeton University Press, 2014)
Examining the democratic-socialist politics of the Second Republic, Edward Berenson delves into the largely unexplored content of the Montagnards' ideology and traces its diffusion and reception in the populist religious culture of rural France. This book shows how the urbanbased Montagnards were able to appeal to rural Frenchmen by advocating doctrines grounded in the ideals and morality of early Christianity. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from th.
Cover; I. The Economic Roots of Politicization; Notes; Bibliography
Description based upon print version of record.
Keywords: Church and state -- France -- History -- 19th century; France -- Church history -- 19th century; France -- Politics and government -- 1830-1848.; France -- Politics and government -- 1848-1852.; Socialism -- France -- History -- 19th century; Church and state -- France -- History -- 19th century; Socialism -- France -- History -- 19th century; France -- Politics and government -- 1830-1848.; France -- Politics and government -- 1848-1852.; France -- Church history -- 19th century; HISTORY / Europe / France; Electronic books